Design morphology in brand logo development: a case study of Gao Cheng Palace Noodle - Ping, Liu; Abdul Aziz, Mohd Nasiruddin; Ismail, Issarezal (Universiti Teknologi MARA, Perak, 2025)
This study explores the role of design morphology in innovating brand logo design, with a focus on "Gao Cheng Palace Noodle" as a cultural case study. Using the principles of "form" and "state" within design morphology, the research applies morphological analysis to deconstruct and reassemble visual and symbolic elements rooted in traditional Chinese culture. The methodology involves extracting cultural motifs, analysing morphological dimensions, and synthesizing them into a unified graphic-text logo design. Findings indicate that design morphology enhances the creativity and cultural expressiveness of brand logos, especially in combining typographic and symbolic elements. This research demonstrates how traditional visual languages can be revitalized through a morphological design framework, offering a practical model for culturally embedded branding strategies and contributing to the evolving discourse on cultural identity in visual communication.